Causes of interruption of bevacizumab therapy in age-related macular degeneration - Nunes,Renata Portella (2010)
PURPOSE: To evaluate the rate and the causes of interruption of bevacizumab intravitreal therapy in patients with exudative age-related macular degeneration (AMD) in a referential eye-care center in Joinville, southern Brazil. METHODS: Retrospective, non-comparative, consecutive case series. Cases included all patients with exudative age-related macular degeneration who were treated with one or more bevacizumab intravitreal injections at Sadalla Amin Ghanem Eye Hospital between January, 2006 and January, 2008. Data were obtained from patients' medical records and telephone interviews. Discontinuity criterion was the absence of patient follow-up after a minimum of 3 months from the last ophthalmic examination. RESULTS: Eighty-two patients were treated. Among them, 24 (29.3%) interrupted follow-up inadvertently. The mean age was 75.2 years old (range 65-89 yo). Mean number of bevacizumab intravitreal injections was 2.0 (range 1-6). Nineteen patients answered to telephone questionnaires. The main alleged causes of discontinuity of therapy were unexpected poor visual results (8 cases, 42.1%), lack of information about followup visits (5 cases, 26.3%) and comorbidities (3 cases, 15.8%). CONCLUSIONS: A high number of patients interrupted follow-up after beginning bevacizumab therapy. Many of them related avoidable causes for discontinuity of treatment. Efforts must be done to improve education of age-related macular degeneration patients, especially in relation to functional outcomes and prolonged follow-up care.